Experiencias de aula con materiales magnéticos y caracterización del magnetismo en la escuela secundaria - Moreno Fernández, Oscar; Basto Rueda, Adonai (Revista Científica, 2011)
The following article is proposed to improve the experience and the relation student-phenomenon, to obtain assumptions for theories of magnetism, recognizing how high school students in grades sixth, tenth and eleven of the school Liceo Normandia cancharacterize the phenomenon of magnetism. This is based on the interaction and observation of certain types of magnetic materials, such as, ferromagnetic and paramagnetic among others. The requirement is from an experimental study, showing the way in the students interpret magnetic phenomenon with simple experiments, obtaining a detailed analysis about ways to explain it.